Kinerja Keuangan dan Internet Financial Reporting Index (IFRI): Sebuah Studi Relevansi Pada Sektor Perbankan Syariah di Kawasan ASEAN - Imanda Firmantyas Putri Pertiwi (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
This study aimed to assess the effect of Islamic Banks financial performance according to the Risk Profile, Good Corporate Governance, Earnings and Capital (RGEC) on the disclosure of financial performance through the company’s website or being known as Internet Financial Reporting Index (IFRI). Taking Islamic banks across the ASEAN region as target of the research, this study result the conclusion that profitability ratios and nonperforming finance are two things that do not affect the index of internet financial report. While CAR and FDR show significant impacts on the index of IFR. These results have been proven their robustnesses. Control variables was added to the model and the results obtained did not change significantly. The total number of Islamic banks in the ASEAN region are 32 banks. Twelve Islamic banks are in Indonesia, 16 in Malaysia, one in the Philippines, one in Thailand and two in Brunei Darussalam. One bank in Brunei being canceled due to incomplete information. The method used in this research is multiple linear regression, furthermore control variables was added to reduce the bias of the research results.